Special Involute-Evolute Partner D-Curves in E3 - Bektas, Ozcan; Yuce, Salim (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2013)
In this paper, we take into account the opinion of involute-evolute curves which lie on fully surfaces and by taking into account the Darboux frames of them we illustrate these curves as special involute-evolute partner D-curves in E-3. Besides, we find the relations between the normal curvatures, the geodesic curvatures and the geodesic torsions of these curves. Finally, some consequences and examples are given.
Keywords: Involute-evolute curve; Darboux frame; normal curvature; geodesic curvature; geodesic torsion; Mathematics